(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Many people still now blame M.S. Gorbachev for the collaps of the USSR. Liberals reproach him for being indecisive and not taking radical measures. Conservatives consider Gorbachev a traitor who colluded with the United States to destroy the USSR. Ordinary people who were able to catch the reign of M.S. Gorbachev, associate it with hunger, shortages of goods and disappointment. Germany considers Gorbachev a savior, since he played one of the key roles in the process of unification of the country. For more advanced political scientists, it is obvious that the merit of M.S. Gorbachev is the fact that he did not allow the scenario of the Civil War, as happened in Yugoslavia. In this article, the authors will present arguments that will prove that the reason for the collapse of the USSR was laid down at its foundation, and the active process of disintegration began back in the distant 1960s, when M.S. Gorbachev had just begun to actively engage in politics, and he could not even imagine that he would someday become the head of the USSR. Ключевые слова: Плановая экономика, Гражданской, нефть, перестройка, дефицит, Центральное статистическое управление, ошибки, заговор.